Tensiomyography-derived contractile parameters in sarcopenic and non-sarcopenic older adults - Pus, Katarina; Kalc, Miloš; Šimunič, Boštjan (Frontiers in Aging, 2026)
BackgroundSarcopenia, the progressive decline in skeletal muscle mass and function, is a major public health concern linked to falls, hospitalization and loss of independence among older adults. Initially defined by reduced muscle mass, later also by reduced muscle strength and function, it is now recognized that standard diagnostic tools do not fully capture complexity of sarcopenia. Tensiomyography (TMG) is a non-invasive method that assesses skeletal muscle contractile parameters, which undergo change with aging and sarcopenia. The aims of this exploratory study are to determine whether TMG could be a method for contractile parameters assessment in sarcopenia classification and to evaluate the relationship between TMG-derived parameters and sarcopenia classification tests.MethodsWe included 654 older adults (70.6% women) and included demographics, sarcopenia classification (EWGSOP2, SDOC), muscle strength (handgrip strength, five sit-to-stand), TMG of three leg muscles, muscle mass (bioimpedance), and physical performance (gait speed, timed up-and-go). MANOVA was used to analyze contractile properties and due to low agreement between classifications, we used both classifications. A partial correlation for each sex was conducted to determine the associations between sarcopenia classification tests and TMG-derived parameters of delay time (Td), contraction time (Tc), radial displacement (Dm) and contraction velocity (Vc), controlling for age.ResultsOne-way MANOVA confirmed difference between sarcopenic and non-sarcopenic participants according to EWGSOP2 and SDOC classifications in TMG-derived contractile parameters in all three muscles, Td was consistently longer and Dm consistently lower in sarcopenic individuals. Post-hoc univariate tests further demonstrated specific differences due to sarcopenia presence. Age-adjusted partial correlations were weak to moderate, ranging between −0.430 and 0.369.ConclusionSarcopenic individuals exhibited longer Td and Tc, and smaller Dm, though not consistently across all muscles. Td was longer in all three muscles, reflecting electromechnical delays linked to aging. Dm was consistently lower, suggesting increased muscle stiffness. Correlations between TMG parameters and sarcopenia classification tests indicated that shorter Td and Tc, higher Dm, and greater Vc were associated with higher muscle volume, muscle strength and performance. The findings indicate that TMG parameters may be associated with neuromuscular degeneration and sarcopenia, supporting further exploration of muscle- and sex-specific differences.